PIMPINAN KOMISI PEMBRANTASAN KORUPSI DAN TANTANGAN PENANGGULANGAN KORUPSI DI ERA 4.0 - Wawan Fransisco (Jurnal Hukum Samudra Keadilan, 2020)
The Corruption Eradication Commission was formed with the main mission of carrying out prevention and law enforcement in eradicating corruption. The Chairperson of the Corruption Eradication Commission (KPK) is the spearhead in tackling corruption in Indonesia. In fact, political transactions in the election of the Corruption Eradication Commission (KPK) leader may be eliminated, so candidates with high integrity can be eliminated. The method in this paper uses the normative legal writing method because it examines the laws and regulations, literature, and journals relating to the material examined, which consists of the type of data obtained in this study is secondary data that is data obtained from library research and documentation , which is the result of research and processing of others, which are already available in the form of literature or documentation. The development of technology is now increasingly rapid where everything is completely digital, this era of sophisticated even even corruption can be digital, therefore the ability of the Corruption Eradication Commission (KPK) must be upgraded according to the times to be able to detect and solve corruption cases that are increasingly complicated transactions